OPTIMIZATION DESIGN OF CABIN STRUT BASED ON ISIGHT AND PYTHON FOR CIVIL AIRCRAFT - FANG Yang; ZHANG WeiWen; ZHANG YangYang (Jixie qiangdu)
In order to achieve lightweight and high efficient load transfer requirements an well as cost reduction in the strut design process of civil aircraft. In this paper,it firstly combines engineering theoretical formulas to develop a calculation program using Python,and then integrates the program into Isight platform. It utilizes multi-island genetic algorithm for optimization analysis,and an iterative optimization process for the follow-up strut analysis is established. In the case of most severe local load during axial compression,considering the actual failure model of the strut,the minimum weight of strut is taken as optimization object and the margin of safety is introduced as constraint condition,then the optimization of cross-section geometry characteristic parameters of typical strut for a certain aircraft type are carried out. Under the condition that load bearing capacity requirement and the minimum weight of strut are both met,an optimized set of cross-section geometric parameters of strut is obtained,and to achieve weight reduction of the strut by 20. 4%,which could provide a guidance for the structural weight loss design of the cabin.